(untitled) (Research, Society and Development, 2022)
Senna spectabilis (Fabaceae-Caesalpinioideae) is a tree species that occurs in northern Minas Gerais and northeastern Brazil, present in caatinga formations with deep and drained soils. It has economic importance as timber, home medicine, ornamental plants, forest restoration, agroforestry and forage systems. The study aimed to understand the effect of Efficient Microorganisms (EM) at different dilutions in breaking dormancy in the germination of Senna spectabilis seeds. To carry out the work, the fruits were collected at Bosque das Arapiracas, in Arapiraca, and then taken to the Forest Resources Laboratory at the Agrifood Technology Pole, where the germination test was carried out. The experiment was carried out in a completely randomized design -DIC carried out in four treatments and 5 replications. Where T1 is the control/control with 100% distilled water; T2 – with 2% bokashi+ distilled water; T3 – with 3% bokashi + distilled water and T4 – with 4% bokashi + distilled water. After the treatments, the seeds were placed to germinate in a germination chamber (BOD). Data were collected and recorded in an Excel spreadsheet for analysis of IE and IVE. Seeds of S. spectabilis sown in 4% bokashi had a good germination index and germination speed. The treatment that obtained the best result was T4, followed by T2 and Treatment 3 with 3% bokashi had the highest seed death rate. The experiment confirmed that it is possible to break seed dormancy using the EM break method.